The Effect of Overconfidence, Representative, Anchoring, and Availability Biases on Investment Decisions and Market Efficiency - Murhadi, Werner Ria; Irvansyah, Daniel; Mahadwartha, Putu Anom (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 18 Nomor 2 Tahun 2024, 2024)
This study looks at how behavioral biases affect investment choices and market efficiency. This research was conducted because many millennials invest on a bandwagon without having a good understanding of investment. This kind of study use the structural equation modeling analysis method. The study's findings indicate that the bias variable overconfidence behavior can strongly influence perceived market efficiency. Nevertheless, choices about investments are unaffected by the overconfidence bias, representational bias, anchoring, and availability behavior. The variable investment decision significantly influences perceived market efficiency. Investors with investment experience above five years and a high income can make a difference in investment decisions chosen by investors. This study theme's practical application relates to the findings of overconfidence bias, which has a substantial detrimental impact on investors' perceptions of market efficiency. A high degree of confidence among investors can lead to illogical judgments and disregarding all dangers, resulting in inefficient market circumstances.   Keyword : anchoring, financial behavior, investment decision, market efficiency, overconfidence